Fluid flow through compressible soft particle beds. Issue 5 (6th January 2016) - Tung, Kuo‐Lun; Chen, Liang‐Hsun; Chen, Yi‐Rui; Lin, Yu‐Shen; Lin, Yi‐Feng; Li, Yu‐Ling
Abstract : The fluid flow through a soft particle bed was studied theoretically and experimentally in this report. Several correction factors were introduced to modify the Ergun equation and account for the deformed shape and reduced volume of compressed particles in a compressible soft particle bed. To acquire the correction factors, both uni‐compression tests and computational fluid dynamics simulation methods were used. The pressure drop estimated from the customized modeling equation was further compared with the experimental data obtained from a bed composed of calcium‐alginate gel particles. In contrast to the conventional Ergun equation, the pressure drop estimated from the customized modeling equation was highly consistent with the experimental data. The result suggests that the customized modeling equation is a convenient tool for accurately predicting the pressure drop across a compressible soft particle bed. © 2016 American Institute of Chemical Engineers AIChE J, 62: 1716–1727, 2016